Power systems - Grigsby, Leonard L. (Boca Raton, Florida : CRC Press, 2012)
The Electric Power Engineering Handbook, Third Edition updates coverage of recent developments and rapid technological growth in crucial aspects of power systems, including protection, dynamics and stability, operation, and control. With contributions from worldwide field leaders--edited by L.L. Grigsby, one of the world's most respected, accomplished authorities in power engineering--this reference includes chapters on: Nonconventional Power Generation, Conventional Power Generation, Transmission Systems, Distribution Systems, Electric Power Utilization, Power QualityPower System Analysis and Simulation, Power System Transients, Power System Planning (Reliability), Power Electronics, Power System Protection, Power System Dynamics and Stability, Power System Operation and Control, Content includes a simplified overview of advances in international standards, practices, and technologies, such as small-signal stability and power system oscillations, power system stability controls, and dynamic modeling of power systems. Each book in this popular series supplies a high level of detail and, more importantly, a tutorial style of writing and use of photographs and graphics to help the reader understand the material. This resource will help readers achieve safe, economical, high-quality power delivery in a dynamic and demanding environment.
Meisner -- Community Considerations, J.H. Sosinski -- Animal Deterrents/Security, M. Stine -- Substation Grounding, R.P. Keil -- Direct Lightning Stroke Shielding of Substations, R.S. Nowell -- Seismic Considerations, E. Fujisaki -- Substation Fire Protection, D. Delcourt -- Substation Communications, D.E. Nordell -- Physical Security of Substations, J. Oglevie, W.B. Dietzman, and C. Smith -- Cyber Security of Substation Control and Diagnostic Systems, D. Thanos -- Gas-Insulated Transmission Line, H. Koch -- Substation Asset Management, H.L. Willis and R.E. Brown -- Station Commissioning and Project Closeout, J. Burke and R. Clarke -- Energy Storage, R. Masiello -- Role of Substations in Smart Grids, S. Borlase, M.C. Janssen, M. Pesin, and B. Wojszczyk
Includes index.
Keywords: ELECTRIC POWER SYSTEMS